European works councils. A transnational industrial relations institution in the making - Waddington, Jeremy (London, 2010)
"The creation of European Works Councils is arguably the most important measure taken in global industrial relations in recent years. European Works Councils and Industrial Relations examines the communication and information-sharing between workers' representatives and top management in multinational firms to assess whether EWCs are achieving their objectives, and whether institution-building has been a second result of the initiative. The book assesses the development of European works councils, the first transnational institutions of employee participation. Drawing on survey data, it shows that European works councils rarely meet the objectives intended for them by the European Commission, and are in the process of long-term development, the outcome of which is uncertain."